Methods and Ways to Achieve Sustainability of the Urban Landscape - Doctor Akromova Mukhlisa Saidmukhtor's Qizi (Peerian Journals Publishing, 2023)
The article deals with the study of the landscape concept, the correct design of landscape solutions, the design codes for all standard projects, the critical characteristics of natural landscapes, the development and sustainability of urban landscape systems
Keywords: Urban planning; design code; landscape